Intelligent Content Recommendation System For NODKN Based On Prime Knowledge Groups - Balavijendran, Logandran (2008)
The core objective of this research is to improve methods to recommend content to users that they might be interested in, to improve their browsing experience, specifically in the domain of multimedia news content.